Are Patients and Their Providers Talking About Long-Acting Injectable Antiretroviral Therapy? Penetration into Clinical Encounters at Three U.S. Care Sites. (11th June 2022) - Christopoulos, Katerina A; Colasanti, Jonathan; Johnson, Mallory O; Diaz Tsuzuki, Manami; Erguera, Xavier A; Flores, Rey; Kerman, Jared; Dance, Kaylin; Sauceda, John A; Neilands, Torsten B; Dilworth, Samantha E; Koester, Kimberly A; et al.
Abstract: Use of long-acting injectable antiretroviral therapy depends on patient awareness, provider discussion, and patient willingness to use. We conducted a postvisit survey with patients at 3 HIV clinics in San Francisco, Chicago, and Atlanta in May 2021 to assess for inequities in these early implementation phases.